STUDY OF TURBULENT MODEL AND NUMERICAL TIME STEPS FOR ACCURACY OF FLOW SOLUTION AROUND CYLINDER - Ihsan (NIM : 13612047), Muhammad
One of the classical problems in fluid mechanics is the determination of the flow field passing through an upright object represented by a circular or rectangular cylinder. The flow around the cylinders has been extensively studied because of its importance in many practical applications, such as heat exchangers, chimneys, hydrodynamic loading on ocean marine piles and supporting legs. The flow around the cylinder is usually subcritical (mixed, transition to turbulent occurring after separation) or critical (turbulent dominated, only part of the boundary layer formed on the surface of the tube is laminar). In a critical flow, the transition to turbulence occurs before separation and turbulence stand out in other boundary layers and in the flow within the bundle. The combination of flow instability and transitional phenomena in the boundary layer makes this type of flow difficult to model numerically. To simulate these flow characteristics appropriately, various turbulent models in CFD are used. In this study, a literature study was conducted to determine the exact turbulent model in the case of flow around the cylinder. Furthermore, a numerical study was conducted to determine the effect of numerical time step size on the simulation accuracy of flow around the cylinder. Results from the previous stage is be used to perform numerical studies to determine the most appropriate turbulent model for the case of flow around the cylinder. All numerical studies were performed in ANSYS Fluent 16.0 software.